U.S. dog and cat owners consumer perception of insect proteins in companion animal feed - Bimonte, Amanda (Kansas State University, 2024)
This research aims to provide insight on how to enhance consumer perception of insect-based pet products. Insect protein is a sustainable alternative to meat proteins that is provides some nutritional components and is safe for dogs and cats. Feeding insects is a new concept for U.S. pet owners and many consumers are uncertain about the ingredients and their impact on pet health. There is a particular “ick-factor” for many people considering feeding their pets something they do not eat themselves. A consumer survey of 509 U.S. dog and cat owners was conducted in December of 2023, and the respondent’s data analyzed using logistic regression models. The paper utilized three main objectives to study consumer behavior when considering and purchasing pet products made with insect-based ingredients. The three objectives are to (i) quantify the attributes of current buyers of insect-based pet food products, (ii) determine which attributes insect pet foods would need to have for potential purchasers, (iii) and review which key facts about insect proteins would increase consumers comfortability feeding it to their pet. The first objective is to establish statistically significant characteristics of current buyers of insect-based pet food products. Survey respondents who identified themselves as being a current or previous purchaser of insect-based pet food products were specified as a dependent variable. A binary logistic regression model was specified and estimated to examine hypothesized correlations between key attributes about respondents and their potential correlations with being current purchaser. The model results indicate a statistically significant relationship between a number of pet owner characteristics, pet food purchasing habits and the likelihood of them being a current purchaser. Some notable factors include living in an urban community, seeking innovative pet products, having purchased plant-based pet food products, seeking sustainable pet food options, having purchased allergy pet food products, having purchased functional health pet products, having purchased insect-based food for themselves, and having purchased allergy specific food for themselves. The second objective of the study is to shed light on the attributes that are important for pet owners when considering purchasing insect-based pet foods. Survey respondents were asked which product features they consider a “must have” in their potential insect-protein based pet food purchasing. After the question about which attributes were a “must have” for each consumer, they were asked “If a pet food made with insect protein met all of your “must haves”, would this change your likelihood of feeding it to your pet?” Respondents reported if they were slightly more likely, very much more likely, or stayed the same. A logistic regression was modeled to test correlations between which “must haves” had a significant impact on increasing their likelihood to purchase insect products if their “must haves” were met. There were two “must haves” that had a statistically significant increase in likelihood of them reporting they are very much more likely to purchased insect-based pet foods. Two statistically significant variables were must have environmentally friendly and must have science-based. The third objective is to gain insight on what facts about insect proteins made consumers more comfortable with the idea of feeding insects to their pet. In this section of the survey, several facts were shared about insect ingredients, and consumers were asked: “For each fact, would this make you more likely to feed pet food made with insect protein to your pet?”. Consumers answered if they were slightly more likely, very much more likely, or if their likelihood stayed the same. After these series of facts, respondents were asked “Have these facts given you enough knowledge to feel comfortable with insect protein in pet food?” Respondents reported if they were fairly comfortable, slightly comfortable, comfortable, very comfortable, or not at all comfortable. A logistic regression was modeled to test several hypotheses between which facts that consumers reported made them very much more likely to purchase insect proteins, statistically correlated with them feeling comfortable or very comfortable feeding insect proteins to their pet. There were two statistically significant facts that increased consumers likelihood to purchase. These related education about aroma and flavor of insect protein and insects being a natural part of a wild cat’s diet.
Keywords: Insect protein; Pet food; Consumer insight; Black soldier fly larvae; Pet owner survey